Prediction of Ground Settlement Induced by Slurry Shield Tunnelling in Granular Soils - Mo'men Ayasrah; Hongsheng Qiu; Xiedong Zhang; Mohammad Daddow (Civil Engineering Journal, 2020)
Underground structures play an important role in achieving the requirements of rapid urban development such as tunnels, parking garages, facilities, etc. To achieve what is needed, new transportation methods have been proposed to solve traffic congestion problems by using of high-speed railway and subway tunnels. One of the issues in urban spaces due to tunnel excavation is considerable surface settlements that also induce problems for surface structures. There are a variety of published relationships concerned with field measurements and theoretical approaches to evaluating the amount of the maximum surface settlement value due to tunneling. This paper studies the ground surface settlement caused by the Greater Cairo Metro – Line 3 - Phase-1. This project was constructed by a slurry shield Tunnel Boring Machine (TBM). Therefore, this work consists of two parts. The first part presents the details of the project and monitoring results field and laboratory geotechnical investigations in order to determine the soil properties. The second part is to the comparison between the field measurements and theoretical approaches for surface settlement due to tunneling construction. At the end of the works, the results show that the more convenient methods which approach the field measurements, and the major transverse settlement occurs within the area about 2.6 times the diameter of the tunnel excavation. Doi: 10.28991/cej-2020-03091617 Full Text: PDF